An Examination and Analysis of the Historical Development of the Local Church Movement from an Asian Woman’s Perspective = 從亞洲女性角度審視和分析地方教會運動的歷史發展 - Chan, Janice (Review of Religion and Chinese Society, 2024)
An examination of the Local Church movement reveals that the major revivalists in the early twentieth century were predominantly women. Yet, most historical sources identify and honor only men as founders and label women as helpers. This has significantly impacted how the church remembers women’s contributions. Although the Local Church often attracts criticism from mainline Protestants because of its unique contextualized theology, members of the communities vigorously defend and advocate for their standpoints. An analysis of the Local Church’s theological development shows that its ecclesiology has been dramatically influenced by the mystical tradition, the Brethren movement, and allegorized and unconventional biblical interpretations of the Local Church. This study engages in a theological dialogue with Veli-Matti Kärkkäinen to call for Christian leaders to widen, deepen, and rethink their understanding of the Local Church movement as its members continue to shape the development of ecclesiology and their practices in the Chinese diaspora.